Working Capital Management: A Review of Concepts and Empirical Evidence in the Nepalese Manufacturing Sector - Regmi, Prakash (Academia Research Journal, 2025)
This study aims to critically examine the impact of working capital management on the profitability of selected manufacturing firms. Nepal. Using financial and statistical tools, including correlation and regression analysis, the research examines the liquidity position, working capital utilization, and the relationship between working capital and profitability for Unilever Nepal Ltd. (UNL), Dabur Nepal Ltd. (DNL), and Himalayan Distillery Ltd. (HDL) over five years (2019/20 to 2023/24).  Key findings highlight certain companies which are struggling with ideal liquidity and are effectively managing working capital. It recommends that firms prioritize effective management of inventory, receivables, and payables to enhance their financial health.